2017
DOI: 10.1021/acschemneuro.7b00303
|View full text |Cite
|
Sign up to set email alerts
|

Studies on 16,17-Pyrazoline Substituted Heterosteroids as Anti-Alzheimer and Anti-Parkinsonian Agents Using LPS Induced Neuroinflammation Models of Mice and Rats

Abstract: Alzheimer's disease (AD) and Parkinson's disease (PD) are the most common forms of neurodegenerative disorders. Dehydroepiandrosterone (DHEA) has been reported as a neuroprotective steroid useful in the therapeutic management of neurodegenerative disorders such as AD and PD. Herein we report the synthesis and evaluation of a new series of 16,17-pyrazolinyl DHEA analogues 2-4a-d as neuroprotective agents using LPS-induced neuroinflammation animal models. Treatment with the pyrazoline substituted steroids consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…In another area of therapeutic interest, two recent studies involving biomedical-steroid function, promise to lead to interesting structure function studies. It was shown that 16,17-pyrazoline substituted heterosteroids [21] and 16-arylideno steroids [22] both represent a new class of neuroprotective agents for the treatment of Alzheimer's and Parkinson's diseases. In particular it was shown that the introduction of a pyrazoline ring at the 16,17 position of the steroid skeleton resulted in improvement of neuroprotective effects.…”
Section: Conclusion and Proposed Future Studiesmentioning
confidence: 99%
“…In another area of therapeutic interest, two recent studies involving biomedical-steroid function, promise to lead to interesting structure function studies. It was shown that 16,17-pyrazoline substituted heterosteroids [21] and 16-arylideno steroids [22] both represent a new class of neuroprotective agents for the treatment of Alzheimer's and Parkinson's diseases. In particular it was shown that the introduction of a pyrazoline ring at the 16,17 position of the steroid skeleton resulted in improvement of neuroprotective effects.…”
Section: Conclusion and Proposed Future Studiesmentioning
confidence: 99%
“…It should be noted that some of these compounds exhibit no significant hormonal activity [28][29][30][31]. Both heterocyclic analogs I [32][33][34][35][36][37][38][39] and carbocyclic analogs II [40,41] of pentacyclic steroids have attracted considerable attention (Scheme 1). Steroids bearing an additional carbocycle annulated at the 16 and 17 positions of the ring D (III) are characterized by unique biological activity [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that some of these compounds exhibit no significant hormonal activity [ 28 , 29 , 30 , 31 ]. Both heterocyclic analogs I [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and carbocyclic analogs II [ 40 , 41 ] of pentacyclic steroids have attracted considerable attention ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years growing interest has been focused on steroidal 2-pyrazolines and pyrazoles due to their antiandrogenic [18] or direct antiproliferative effect [19,20,21] or their ability to inhibit one of the key regulatory enzymes of steroid biosynthesis [22,23,24,25], which makes them potential candidates for the chemoprevention or treatment of cancerous diseases. Some further derivatives are also known to possess neuroprotective [26], antimicrobial [27] or insecticidal activity [28] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%